PENGGUNAAN KONTROL PID DENGAN BERBAGAI METODE UNTUK ANALISIS PENGATURAN KECEPATAN MOTOR DC - Iftitah, Iftitah; Irhas, Muhammad; Azizah Ilham, Siti Asyiqah (Universitas Islam Negeri Alauddin Makassar, 2020)
DC motor is a motor tha is widely applied to industrial and household equipment because of the level of flexibility and fairly easy operation. But in terms of speedDC motrs have the disadvantage that the speed is not constant along with the addition of the load so to overcome this problem a controller is needed in order to obtain a constant speed in accordance with the desired set poit. PID control is a control that serves to minimize the error rate of a plant. This control consists of Controller parameters P, I, D where the value of this parameter determines the level of response of a control to the plant. So it is necessary to engineer the tuning parameters with various methods so that the value of a parameter is in accordance with the palnt. Based on the description above, the purpose of this study is to review various tuning methods in response to the response of a DC motor.Â Â